ANALISIS MORFOMETRIK DAN MERISTIK NILA (Oreochromis sp.) STRAIN LARASATI F5 DAN TETUANYA - Muhotimah Muhotimah; Bambang Triyatmo; Susilo B. Priyono; Toni Kuswoyo (Jurnal Perikanan Universitas Gadjah Mada, 2013)
Cross-breeding between Janti’s Black Tilapia (female parent) and Janti’s White Tilapia (male parent) has been performed by Institution of Germination and Freshwater Fish Farming which is located at Janti Village – District of Klaten and produced Tilapia Larasati (Red Tilapia Strain Janti) F5. This study aimed to compare the Tilapia Larasati F5 and it parents based on morphometric and meristic characters, and to know the length-weight relationship of three strains of tilapia. Analysis of morphometric characters performed by Principal Component Analysis (PCA) while the meristic character analyzed descriptively by reviewing the literature. Kinship of three strains were tested by cluster analysis while length-weight relationship analysis was conducted to determine the pattern of ﬁ sh growth and condition factor . The scatter plot results of the 12 morphometric characters showed that Tilapia Larasati F5 has a similar body form with Janti’s Black Tilapia and has a slightly different form of Janti’s White Tilapia especially in the part of head. Tilapia Larasati F5 and Janti’s Black Tilapia obtained on a longer body, longer forehead, longer jaw (big mouth), and long face and long nose. It result supported by cluster analysis which showed that Tilapia Larasati F5 has a closer kinship distance to Janti’s Black Tilapia viewed from morphometric characters. Analysis of meristic characters showed that the number of scales on the dorsal ﬁ n in front of the Tilapia Larasati F5 and Janti’s Black Tilapia amounted to more than the Janti’s White Tilapia. Third tilapia strains had isometric growth pattern. Analysis of the value of condition factor indicates that Tilapia Larasati F5 has the best body condition.